2016
DOI: 10.1002/hed.24611
|View full text |Cite
|
Sign up to set email alerts
|

Flex Robotic System in transoral robotic surgery: The first 40 patients

Abstract: Lesions in the oropharynx, hypopharynx, or supraglottic larynx could be successfully resected using the Flex Robotic System, thus making the system a safe and effective tool in transoral robotic surgery. © 2016 Wiley Periodicals, Inc. Head Neck 39: 471-475, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 20 publications
(33 reference statements)
0
46
0
2
Order By: Relevance
“…Lang et al also demonstrated excellent access to the oropharynx and larynx, finding that 75 of 80 patients with malignancies were accessible for resection with the Flex system. Importantly, there is a reasonable average setup time of between 9 and 12.4 minutes, a data point on the system's practicality . These studies demonstrated the utility of this technology in TORS, however, more research is needed to better evaluate and understand the efficacy and safety profile of this technology.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Lang et al also demonstrated excellent access to the oropharynx and larynx, finding that 75 of 80 patients with malignancies were accessible for resection with the Flex system. Importantly, there is a reasonable average setup time of between 9 and 12.4 minutes, a data point on the system's practicality . These studies demonstrated the utility of this technology in TORS, however, more research is needed to better evaluate and understand the efficacy and safety profile of this technology.…”
Section: Introductionmentioning
confidence: 84%
“…Very little literature, none from the United States, exists to assess the Flex system's performance in humans. In a prospective study (N = 40), Mattheis et al (2016) demonstrated excellent transoral visualization with the Flex system. They showed that 95% of the T1 and T2 carcinomas of the oropharynx, hypopharynx, and supraglottis in their cohort were accessible, allowing for oncologically sound resections without any serious adverse events.…”
Section: Introductionmentioning
confidence: 97%
“…14 Improved access to the larynx and decreased surgical morbidity are regarded as the main potential benefits. 19,20 In particular, access to the anterior commissure of the larynx by TORS has been described as highly challenging. 15,16 For the laryngeal space in particular, the number of published surgical cases is comparatively small, and only a few successful applications have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Other manufacturers have already sought to overcome these limitations using a flexible and adaptable construction. For instance, the Flex® System (Medrobotics, Raynham, USA) shows promising results, and successful clinical use of this commercially available system has been reported with some restrictions …”
Section: Introductionmentioning
confidence: 99%